Lost unicorns of the velvet revolutions : heterotopias of the seminar - Nikolchina, Miglena (Fordham University Press, 2012)
"This book examines the eastern European seminar of the late 1980s and early 1990s-an ongoing academic meeting place outside the formal rubric of the university-tracing its evolution into a social movement on the street and identifying the political force of the theoretical conversations that took place there. It also shows how these theories reflect the loss of socialist idealisms and established materialist frameworks that eventually evolved into a set of heterotopic visions with a fundamentally altered sense of materialism. It provides both glimpses of a genuinely alternative world to the Western academy that its denizens are so prone to critique, one in which oral discourse and dialogism were especially prominent values, and a utopian view of the Western intellectual world from that now-lost space."--Project Muse.